Structure-Function Relationship of the Ryanodine Receptor Cluster Network in Sinoatrial Node Cells - Alexander V. Maltsev; Valeria Ventura Subirachs; Oliver Monfredi; Magdalena Juhaszova; Pooja Ajay Warrier; Shardul Rakshit; Syevda Tagirova; Anna V. Maltsev; Michael D. Stern; Edward G. Lakatta; Victor A. Maltsev (Cells)
The rate of spontaneous action potentials (APs) generated by sinoatrial node cells (SANC) is regulated by local Ca2+ release (LCR) from the sarcoplasmic reticulum via Ca2+ release channels (ryanodine receptors, RyRs). LCR events propagate and self-organize within the network of RyR clusters (Ca release units, CRUs) via Ca-induced-Ca-release (CICR) that depends on CRU sizes and locations: While larger CRUs generate stronger release signals, the network’s topology governs signal diffusion and propagation. This study used super-resolution structured illumination microscopy to image the 3D network of CRUs in rabbit SANC. The peripheral CRUs formed a spatial mesh, reflecting the cell surface geometry. Two distinct subpopulations of CRUs were identified within each cell, with size distributions conforming to a two-component Gamma mixture model. Furthermore, neighboring CRUs exhibited repulsive behavior. Functional properties of the CRU network were further examined in a novel numerical SANC model developed using our experimental data. Model simulations revealed that heterogeneities in both CRU sizes and locations facilitate CICR and increase the AP firing rate in a cooperative manner. However, these heterogeneities reduce the effect of β-adrenergic stimulation in terms of its relative change in AP firing rate. The presence of heterogeneities in both sizes and locations allows SANC to reach higher absolute AP firing rates during β-adrenergic stimulation. Thus, the CICR facilitation by heterogeneities in CRU sizes and locations regulates and optimizes cardiac pacemaker cell operation under various physiological conditions. Dysfunction of this optimization could be a key factor in heart rate reserve decline in aging and disease.